Identification of pyrvinium pamoate as an anti-tuberculosis agent in vitro and in vivo by SOSA approach amongst known drugs. Issue 1 (1st January 2020) - Guan, Qing; Zhan, Lingjun; Liu, Zhi-Hao; Pan, Qin; Chen, Xu-Lin; Xiao, Zhen; Qin, Chuan; Zhang, Xiao-Lian
ABSTRACT: Tuberculosis (TB), caused by Mycobacterium tuberculosis ( M.tb ) bacteria, is a leading infectious cause of mortality worldwide. The emergence of drug-resistant M. tb has made control of TB more difficult. The selective optimization of side activities (SOSA) approach uses old drugs for new pharmacological targets. In the present study by using SOSA approach, we have successfully identified pyrvinium pamoate (PP) which is capable of inhibiting the growth of mycobacteria, including M. tb H37Rv, Mycobacterium smegmatis, Bacille Calmette-Guérin (BCG), M. tb H37Ra, and drug-resistant M. tb clinical isolates in vitro from 1280 known drugs library. The MIC99 of PP, the minimum inhibitory concentration that inhibits more than 99% of M. tb H37Rv and the drug-resistant M. tb clinical isolates, ranges from 1.55 to 4.8 µg/mL. Importantly, PP could reduce the bacterial colony-forming units (CFUs) in lung, spleen and liver tissues, and effectively inhibit inflammatory response in M. tb H37Rv, multidrug-resistant (MDR) M. tb and extensively drug-resistant (XDR) M.tb -infected mice. Our results clearly show that the PP has the potential application for treatment of TB.